2011
DOI: 10.1176/appi.ajp.2011.11010094
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Study of Self-Regulatory Control and Conflict Resolution in Adolescents With Bulimia Nervosa

Abstract: Objective The authors examined functional activity in the frontostriatal systems that mediate self-regulatory capacities and conflict resolution in adolescents with bulimia nervosa. Method Functional magnetic resonance imaging was used to compare blood-oxygen-level-dependent response in 18 female adolescents with bulimia nervosa and 18 healthy female age-matched subjects during performance on a Simon spatial incompatibility task. Bayesian analyses were used to compare the two groups on patterns of brain acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
168
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(189 citation statements)
references
References 20 publications
14
168
4
1
Order By: Relevance
“…26 However, 2 previous studies addressing general cognitive inhibition in adolescents and adults support diminished activity in the frontostriatal network during inhibitory control. 27,28 In the present study, significant differences within frontostriatal networks were observed only in patients with bulimia nervosa with 3 or more binge eating/purging episodes per week. Patients with less severe symptoms showed no significant neural alterations compared with healthy controls and patients with high symptom severity.…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…26 However, 2 previous studies addressing general cognitive inhibition in adolescents and adults support diminished activity in the frontostriatal network during inhibitory control. 27,28 In the present study, significant differences within frontostriatal networks were observed only in patients with bulimia nervosa with 3 or more binge eating/purging episodes per week. Patients with less severe symptoms showed no significant neural alterations compared with healthy controls and patients with high symptom severity.…”
Section: Discussioncontrasting
confidence: 39%
“…Previous studies investigating cognitive inhibition 27,28 have identified diminished activation of the right lateral PFC and striatum as core regions of impaired inhibitory control in patients with bulimia nervosa. A meta-analysis 48 has identified clusters of activation in the PFC, pre-SMA and insula during behavioural inhibition.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This probability is displayed in a Posterior Probability Map. Because the Bayesian method infers posterior probability, by definition, it does not generate false positives and therefore does not require adjustment of its p-values based on p-value thresholding, as shown previously (Friston and Penny, 2003;Marsh et al, 2011). We adopted a similar approach as in Klein et al (2007) but with a more stringent threshold.…”
Section: Statistical Analyses Of Functional Imaging Datamentioning
confidence: 99%